Transformation of Whey Waste in the Development of Sustainable Functional Compound-Based Food and Non-Food Products: Transformasi Limbah Whey dalam Pengembangan Produk Pangan dan Non Pangan Berbasis Senyawa Fungsional Yang Berkelanjutan - Irfan Fadhlurrohman; Dewi Wulandari; Rakha Yudhistira; Amelia Fitaguri; Muhammad Reyfal Benita Chaniago; Lutfi Bagus Setiawan; Triana Setyawardani; Juni Sumarmono (Universitas Muhammadiyah Sidoarjo, 2026)
Whey waste is a by-product of the dairy processing industry that has the potential to cause environmental pollution, but still contains valuable nutrients such as protein, lactose, and minerals. This study aims to review the utilization of whey in the development of food and non-food products based on functional compounds. The method used was a literature review of several scientific journals with a qualitative descriptive approach. The results showed that whey can be processed into various food products such as fermented beverages, probiotics, yogurt, nata, and crackers, as well as non-food products such as bioplastics, biofoam, and bioethanol. The utilization of whey has been proven to increase the economic value of waste while reducing environmental pollution.